Socioeconomic Status and Behavioral Problems in Children: The Mediating Effect of Social Relations in Mainland China - Jingya Nong; Pinghua Zhu; Xi Li; Peipei Chai; Tiemin Zhai; Yuhui Zhang (MDPI AG, 2022)
In 2014, 13.33% of youths aged 5-19 years worldwide had at least one type of behavioral problem. In China, children may be more likely to have internal and external behavioral problems, given that China has a high number of "left-behind children" and "only child of the family". In this study, we explore the relationships between socioeconomic status (SES), social relations, and childhood behavioral problems in China. Data from 2151 children aged 10-15 years were collected from the 2018 wave of the China Family Panel Studies. We conducted structural equation modeling (SEM) using Amos (version 26) to test a theoretical model. The results showed that SES was significantly related to childhood behavioral problems, and that social relations mediated the relationship between SES and childhood behavioral problems. On the basis of these findings, we discuss relevant theoretical and practical implications.